Radiation induced graft copolymerization of amine-containing monomer onto polyethylene coated propylene for CO2 adsorption - Zubair, N.A. (Institute of Physics Publishing, 2020)
Modification of polyethylene coated polypropylene by radiation-induced graft copolymerization (RIGP) of N-vinylformamide film followed by hydrolysis was studied to produce polyvinylamine (PVAm) containing adsorbent for CO2 adsorption. A number of grafting parameters such as irradiation dose, monomer concentration, and reaction temperature were investigated to obtain desired degree of grafting (DOG) prior to hydrolysis. The DOG was found to be a function of reaction parameters and achieved a desired value of 131 at 40 wt NVF concentration in toluene, 300 kGy dose, 70Â°C temperature and 1h reaction time. Subsequently the hydrolysis of formamide groups in the grafted films into amine functionalities was carried out in basic medium. Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) confirmed the NVF monomer was successfully grafted on PE/PP and consequently the hydrolysis of amide into amine functionalities has occurred in the grafted substrates. The CO2 adsorption capacity of PVAm modified adsorbent was brought to be a function of DOG, which is corresponding to the amine content after hydrolysis. The adsorbent showed the highest CO2 adsorption capacity of 1.32 mmol/g when tested with gas composition of 40 CO2 and 60 nitrogen at room temperature. Â© Published under licence by IOP Publishing Ltd.